Sixty and Shut Out: When Financial Regulation Becomes Financial Exclusion (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Age-based mortgage lending restrictions represent a critical yet understudied dimension of financial exclusion in aging societies. This study combines empirical comparative policy analysis with normative evaluation, documenting international regulatory variation while advancing policy reform arguments grounded in discrimination theory and institutional economics frameworks.This study examines how central bank policy and governmental inaction can perpetuate systematic discrimination against older borrowers through regulatory vacuum rather than deliberate design. Employing qualitative comparative policy analysis across ten jurisdictions, the United States, Canada, United Kingdom, Australia, Switzerland, Singapore, France, Spain, Turkey, and Sri Lanka, we construct a five-tier regulatory ranking that reveals stark divergence unaccountable by economic development or demographic differences alone. Sri Lanka’s rigid 60-year mortgage age cutoff, the most restrictive approach identified globally, categorically excludes creditworthy older borrowers. Drawing on discrimination theories in the critical paradigm, we further establish that Sri Lanka’s approach constitutes statistical discrimination.Cross-national evidence from 180 countries analyzed by Barth, Caprio, and Levine (2013) using comprehensive bank regulation and supervision data (rom1999-2011) reveals no statistically significant correlation between age-based lending limits and loan portfolio performance metrics, undermining the prudential rationale for categorical cutoffs, revealed neither significant predictors of portfolio quality (β = 0.023, p > 0.10) nor associated with lower default rates when controlling for other underwriting standards. Maintaining current policies guarantees escalating financial exclusion for a growing, economically active aging population, hence this desk research advances a sequenced reform agenda: immediate central bank guidance prohibiting categorical age denials, short-term development of retirement-appropriate mortgage products, medium-term legislative reform establishing explicit anti-discrimination protections, and long-term institutional strengthening through superannuation system.